Social Phenomena of Smokers with the Incidence of Upper Respiratory Tract Infections in Toddlers at Moncongloe Health Center, Makassar - Wulandari, Ria; Rimbawati, Yazika; Nurhayati, Nurhayati; Fatany, Alief Ihram; Sari, Rini Gustina; Dunggio, Abdul Rivai Saleh (International Journal of Health Sciences, 2024)
Cigarettes are one of the biggest contributors to the causes of death that are difficult to prevent in society. The compounds that make up cigarettes that can affect users are alkaloids which are stimulants, including: nicotine, nicotine, anabasin, myosmin. ARI (acute respiratory tract infection) is an inflammatory process caused by viruses, bacteria, atpicals (mycoplasma), or aspiration of foreign substances involving one or all parts of the respiratory tract. The upper respiratory tract (upper airway) consists of the nose, pharynx and larynx. The lower respiratory tract consists of the bronchi, bronchioles, and alveoli. The aim of this research was to determine the presence of smokers and the incidence of acute respiratory infections in toddlers at the Moncongloe Health Center, Makassar. This type of research is quantitative research with a non-experimental design method using a Cross Sectional research design, which was obtained using the Accidental Sampling technique, namely a sampling technique taken based on the availability of elements and ease of obtaining them, then a Chi Square statistical test was carried out with a significance value of α=0.05. The results of the study showed that there was a relationship between the presence of smokers and the incidence of ISPA in toddlers at the Moncongloe Makassar Community Health Center (p = 0.000). The research conclusion shows that there is a relationship between the presence of smokers and ISPA in toddlers at the Moncongloe Makassar Health Center. Therefore, it is necessary to educate about the impact of smoking on public health, especially for toddlers.